Linguistic Landscape at Triatma Mulya University, Dalung, Kuta Utara, Bali (Unit Pelayanan Bahasa, Politeknik Pariwisata Bali, 2026)
Linguistic Landscape is the visibility and salience of languages on public and commercial signs in a given territory or region (Landry and Bourhis, 1997: 23). The language of public roads signs, advertising billboards, street names, place names, commercial shop signs, and public signs on government buildings combines to form the linguistic landscape of a given territory, region, or urban agglomeration, (Landry and Bourhis, 1997: 25). This study analyzes the linguistic landscape around the Triatma Mulya University Campus, Dalung, Nort Kuta, Bali. The research data is in the form of words, phrases, and sentences in the linguistic landscape found around the Triatma mulya University Campus, Dalung, North Kuta Bali. The data source comes from the researcher's personal documentation of lingusitic signs found on the Triatam Mulya University Campus, Dalung, North Kuta, Bali. This study aims to determine the language variations that occur in linguistic signs found on the Triatama Mulya University Campus, Dalung, North Kuta, Bali, and to determine the intent and meaning of these linguistic signs. The results of this study found that there are 2 language variations in linguistic landscape: Indonesian and English, with Indonesian being the most dominant. These linguistic landscapes are intended for all campus residents, particularly students at Triatma Mulya University, Dalung, North Kuta, Bali.